Isolation, identification, and evaluation of the antioxidant properties of lactic acid bacteria strains isolated from meat environment - Szymanski, Piotr; Okon, Anna; Lepecka, Anna (PloS one, 2025)
Oxidative stress is a condition in which the body loses balance between the production of free radicals and the body’s ability to neutralize them. The role of antioxidants is to protect cells and tissues from the harmful effects of excessive amounts of free oxygen radicals. Lactic acid bacteria (LAB) can exhibit significant antioxidant properties which is the subject of research by many scientists. The aim of the work was isolation, phenotypic and genotypic identification, and evaluation of the antioxidant activity of twenty-one bacterial strains from raw fermented beef hams and the environment of a meat factory. The bacteria were screened in vitro by investigating their DPPH (1,1-diphenyl-2-picrylhydrazyl) and ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) free radical scavenging activity, superoxide anion tests, hydroxyl radical resistance, superoxide dismutase and catalase activity, and hydrogen peroxide resistance. As a result of the conducted research, 21 bacterial strains were isolated. They were assigned to Lactiplantibacillus plantarum (14), Lactiplantibacillus pentosus (3), Lactiplantibacillus argentoratensis (2), Lacticaseibacillus paracasei (1), and Pediococcus pentosaceus (1). The strains were compared with each other and some of them were able to scavenge free radicals DPPH (1.08–36.91%), ABTS (11.24–51.05%), and superoxide anions (3.04–96.70%). Furthermore, resistance to high concentrations of hydrogen peroxide (0.4–1.0 mM H 2 O 2 ) and hydroxyl radicals (25.90–99.22%) has been demonstrated. Some strains produced superoxide dismutase, while none of them produced catalase. The findings indicated that some LAB strains could be promising starter candidates with antioxidant properties.